2015
DOI: 10.1021/acsami.5b00134
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Nanoscale Pt Electrode Agglomeration at the Triple Phase Boundary

Abstract: Nanoporous platinum electrode thin films were delaminated from yttria-stabilized zirconia (YSZ) substrates via double cantilever beam delamination to reveal the structure located at the interface between electrode and electrolyte. The thermally driven morphological evolution between the electrode top surface and the substrate contact interface of agglomerated nanoporous platinum thin films were compared. We found the temperature required for significant agglomeration to occur was approximately 100 °C higher at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…The as‐deposited Pt grains show an average width of ∼15 nm (Figure S5) and the Pt grains on single‐crystal YSZ substrate coalesce with each other after operation for 20 h at 450 °C, causing a significant increase in the average grain width to ∼71 nm (Figure a). In the nanoSDC sample however, the bottom part of columnar Pt grains appears to be much more intact than the top surface of the Pt grains after operation (Figure b), and shows the presence of nanopores (white dotted arrows in the inset image) . By virtue of a hindered coarsening at the Pt‐nanoSDC interface, nanoscale pores survive even after prolonged operation at elevated temperatures (inset image of Figure b), which helps to maintain the TPB density, and consequently, the electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The as‐deposited Pt grains show an average width of ∼15 nm (Figure S5) and the Pt grains on single‐crystal YSZ substrate coalesce with each other after operation for 20 h at 450 °C, causing a significant increase in the average grain width to ∼71 nm (Figure a). In the nanoSDC sample however, the bottom part of columnar Pt grains appears to be much more intact than the top surface of the Pt grains after operation (Figure b), and shows the presence of nanopores (white dotted arrows in the inset image) . By virtue of a hindered coarsening at the Pt‐nanoSDC interface, nanoscale pores survive even after prolonged operation at elevated temperatures (inset image of Figure b), which helps to maintain the TPB density, and consequently, the electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…To test the functionality of the nanostructured BSCF thin film as a SOFC cathode at temperatures below 500 • C, BSCF thin film was deposition on a 200 µm-thick (100) single crystal YSZ, with the typical nanoporous Pt thin film deposited by RF sputtering as an anode [110]. A reference sample with nanoporous Pt cathode is fabricated and tested with the same condition.…”
Section: Thin Film Sofc Fabrication and Electrochemical Characterizationmentioning
confidence: 99%
“…It is reported the thermallydriven morphological evolution between the top surface and the substrate contact interface of agglomerated nanoporous Pt electrode using double cantilever beam technique and found that the temperature required for significant agglomeration to occur was approximately 100 °C higher at the electrolyte contact interface side than at the top surface side. 39 This is because the unbounded surface of Pt is free to migrate under the thermally driven effect whereas the bonded interfacial Pt to the electrolyte experienced a constraint to migrate. 39 This reported work further clearly informed us that the thermal agglomeration behaviors are different from various part of the thin film electrode Figure 2.15 The Pt/YSZ/O2: interfaces and factors controlling the electrochemical behavior 52 Following sessions will discuss the work has been done for improving the thermal stability of nanoporous Pt electrode at high temperatures.…”
Section: System Integrationmentioning
confidence: 99%
“…39 This is because the unbounded surface of Pt is free to migrate under the thermally driven effect whereas the bonded interfacial Pt to the electrolyte experienced a constraint to migrate. 39 This reported work further clearly informed us that the thermal agglomeration behaviors are different from various part of the thin film electrode Figure 2.15 The Pt/YSZ/O2: interfaces and factors controlling the electrochemical behavior 52 Following sessions will discuss the work has been done for improving the thermal stability of nanoporous Pt electrode at high temperatures. The discussed segments are categories as:…”
Section: System Integrationmentioning
confidence: 99%
See 1 more Smart Citation